From Security to Peace and Concord: The Building of a Free Commonwealth in Spinoza's Political Treatise. Issue 159 (1st July 2019) - Visentin, Stefano
Abstract : The aim of this article is to discuss how Spinoza's Theological- Political Treatise and Political Treatise deal with the development of a free and pacific commonwealth, taking into account both a comparison with the irenic tradition of Erasmus and the original position of Spinoza's republicanism within the Dutch context of that period. To approach this issue, comparing Spinoza's idea of security with the Hobbesian one can also be useful in order to demonstrate that security and freedom are not antithetical in Spinoza (differently from Hobbes) but rather support each other. Consequently, the role of peace and concord within the Political Treatise shall be considered the result of a collective self-emendation process of social interactions and political institutions. In this perspective, Spinoza's concept of peace seems a very original attempt to build a free political community, where democratic institutions are both the cause and effect of pacific (i.e., rational and harmonious, although not necessarily irenic) relationships among citizens.